2008
DOI: 10.1021/nl803182c
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Benefits of Rapid Growth Rate for III−V Nanowires

Abstract: In conventional planar growth of bulk III-V materials, a slow growth rate favors high crystallographic quality, optical quality, and purity of the resulting material. Surprisingly, we observe exactly the opposite effect for Au-assisted GaAs nanowire growth. By employing a rapid growth rate, the resulting nanowires are markedly less tapered, are free of planar crystallographic defects, and have very high purity with minimal intrinsic dopant incorporation. Importantly, carrier lifetimes are not adversely affecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
120
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 130 publications
(136 citation statements)
references
References 71 publications
16
120
0
Order By: Relevance
“…A detailed description regarding the growth of GaAs NWs has been reported elsewhere. 27,28 The morphology of GaAs NWs was characterized using a ZEISS Auriga scanning electron microscope (SEM). SEM characterization showed that the cross sections of the NWs are of hexagonal geometry.…”
mentioning
confidence: 99%
“…A detailed description regarding the growth of GaAs NWs has been reported elsewhere. 27,28 The morphology of GaAs NWs was characterized using a ZEISS Auriga scanning electron microscope (SEM). SEM characterization showed that the cross sections of the NWs are of hexagonal geometry.…”
mentioning
confidence: 99%
“…In an MOCVD system, the morphological and crystal properties of the III-V nanowire are commonly controlled by tuning the growth temperature, V/III ratio, and precursor flow rate. [17][18][19] Recently, efforts have been devoted to controlling nanowire growths by varying the properties of the catalysts. 20,21 It has been demonstrated by controlling the shape of Au catalysts, the growth kinetics of InAs nanowires can be enhanced.…”
mentioning
confidence: 99%
“…34 and 38-40) and donoracceptor pair (DAP) peak at 1.48-1.49 eV. 24,38,40 The DAP peak is commonly associated with carbon, 38,40 which is an inherent impurity in MOVPE. As discussed above, Zn is expected to be incorporated in the NWs.…”
Section: Resultsmentioning
confidence: 99%